AN ECONOMIC STUDY OF THE FACTORS AFFECTING THE FOOD SECURITY COEFFICIENT OF THE RICE CROP IN IRAQ FOR THE PERIOD (2003-2020) - Duaa. A. N,; O. K. Jbara, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
This research was aimed to study the most important factors affecting the food security coefficient in Iraq for the period 2003-2020. Where the food security coefficient was calculated for the rice crop, the results showed that the rice food security coefficient amounted to about 0.55, which is nearly enough for six months, which requires maintaining the level of food security of rice and then study the factors affecting food security, considering the food security factor as a dependent variable, and each of the population, local production, available for consumption and imported quantities of rice as independent variables. Statistical and standard methods were used to find out the most important aspects of this subject in the agricultural sector, and Johansen's co-integration method was employed for this purpose, and unit root tests such as Phillips - Perron used, for the purpose of determining the stability of the data and then testing the optimal analysis method and formulating the standard model. The most important finding of the analysis is that there is an equilibrium relationship and a joint integration between the food security factor of rice and each of (population, local production, available for consumption, quantity of imports) despite the presence of short-term unequilibrium, and the value of the error correction parameter was (-1.48) which It means that 148% of the errors or unequilibrium that occur in the short term can be automatically corrected in less than a year to reach equilibrium in the long term.